Pentingnya Pendidikan Etika Berteknologi (Ethical Tech) Bagi Siswa Madrasah - Ali Ridho; Mufiqur Rahman (LPTNU Sumenep, 2024)
This research aims to elucidate the importance of ethics in the use of technology among students in Islamic schools (madrasah), particularly within the context of religious scholarship. Madrasah students are expected to serve as examples for society by emphasizing noble conduct (akhlakul karimah) in their digital technology usage, such as acting as a counterbalance to the dissemination of false information (hoaxes), rather than becoming part of the problem. The research methodology employed is qualitative, utilizing a literature review approach, wherein the researcher collects and analyzes various relevant sources of reference. The research findings indicate that madrasah students are not only required to be proficient in using technology but also accountable for their usage. They are expected to set an example for society in applying ethical values in digital technology.